Perbandingan Penurunan IMT Pasien Obesitas Morbid yang dilakukan Bedah Bariatrik dan Non-Bedah - Clara Valentia Josephine; Novelia Ratna Ury; Suparto Suparto (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Morbid obesity has become a public health problem. Fifty-five million adults are morbidly obese. Several treatment are offered, including non-surgical and bariatric procedures. Treatment outcomes are assessed from the patient's Body Mass Index (BMI), which in general will decrease. The aim of this literature review is to compare the reduction in BMI of morbidly obese patients undergoing bariatric and non-surgical procedures. The method of this literature review is descriptive literature review of eight journals selected based on eligibility criteria. Based on the literature review, from 1.903 participants who were given surgical and non-surgical interventions, the decrease of BMI precentage in RYGB bariatric surgery patients is 27.7%-62.9% higher more than non-surgical therapy which only 5%. In addition, bariatric surgery has the advantage of losing weight in a faster time and lasting in the long term. Bariatric surgery is the first choice in patients with morbid obesity.